Transformative Religious Experience: A Phenomenological Understanding of Religious Conversion, by Joshua Iyadurai - Nichols, Michael D. (Religions of South Asia, 2018)
Transformative Religious Experience: A Phenomenological Understanding of Religious Conversion, by Joshua Iyadurai. Eugene, OR: Pickwick Publications, 2015. xii + 254 pp. ISBN 978-1-620-32746-3 (pb).